Hubungan Peran Teman Sebaya dengan Perilaku Pencegahan Infeksi Menular Seksual di Kalangan Remaja - Nur Layla; Hardin La Ramba; Shinta Prawitasari (Jurnal Gema Keperawatan, 2026)
Adolescents are a population vulnerable to sexually transmitted infections (STIs) due to their involvement in risky sexual behaviors. One factor that is believed to be associated with STI prevention behavior is the role of peers. This study aimed to analyze the relationship between peer roles and STI prevention behavior among adolescents. This research employed a quantitative method with a cross-sectional design. The sample consisted of 92 students from Al-Miftahiyyah Vocational High School, North Jakarta, selected using a stratified random sampling technique. Data were collected using validated and reliable questionnaires measuring peer roles and STI prevention behavior. Data analysis was conducted using the Spearman Rank correlation test. The results showed that the majority of respondents were male (63,0%), aged 18 years (35,9%), and enrolled in grade XI (39,1%). The mean score for peer roles was 22.80, while the mean score for STI prevention behavior was 25,35. The Spearman Rank correlation test revealed a significant positive relationship between peer roles and STI prevention behavior (r = 0,257; p = 0,013). The correlation coefficient indicated a weak relationship between the two variables. This study concludes that better peer roles are associated with better STI prevention behavior among adolescents. Therefore, schools and healthcare professionals are encouraged to develop peer-based reproductive health education programs to improve STI prevention behavior among adolescents.